From research to licensure and beyond: clinical development of MenB-FHbp, a broadly protective meningococcal B vaccine. (3rd June 2018) - Perez, John L.; Absalon, Judith; Beeslaar, Johannes; Balmer, Paul; Jansen, Kathrin U.; Jones, Thomas R.; Harris, Shannon; York, Laura J.; Jiang, Qin; Radley, David; Anderson, Annaliesa S.; Crowther, Graham; et al.
ABSTRACT: Introduction : Given the characteristics of meningococcal carriage and transmission and the sudden, often severe onset and long-term consequences of disease, vaccination can most effectively provide large-scale control of invasive disease. Six serogroups (A, B, C, W, X, and Y) cause nearly all meningococcal disease globally. Capsular polysaccharide conjugate vaccines can prevent serogroups A, C, W, and Y disease. More recently, recombinant protein vaccines for preventing serogroup B meningococcal (MenB) disease have become available, with a major target of vaccine-induced immune response for both vaccines being bacterial factor H binding protein (FHbp). Importantly, FHbp segregates into only two distinct subfamilies (A [also classified as variants 2 and 3] and B [variant 1]). This review summarizes the complete clinical development program supporting licensure of MenB-FHbp (Trumenba®, Bivalent rLP2086), the only MenB vaccine containing antigens from both FHbp subfamilies. Areas covered : Eleven published clinical studies assessing MenB-FHbp efficacy and safety among 20, 803 adolescents and adults are examined. Particular focus is on the methodology of immunogenicity assessments used as a surrogate for clinical efficacy. Expert commentary : Clinical studies in adolescents and adults consistently demonstrated MenB-FHbp safety and induction of immunologic responses against antigenically and epidemiologically diverse MenB isolates, supporting licensure and immunization recommendations.